PENERAPAN PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X PADA MATERI IKATAN KIMIA DI SMK NEGERI 1 GANDAPURA - Ernawati, Ernawati; Amiruddin, Amiruddin; Salfiyadi, Teuku (JGK (Jurnal Guru Kita), 2022)
Abstract: Application of Numbered Heads Together (Nht) Learning to Improve Class X Students' Learning Outcomes on Chemical Bonds at Smk Negeri 1 Gandapura. This research was conducted by giving a pre-test to students to determine students' initial abilities before learning, then subjected to the Numbered Heads Together (NHT) learning model treatment on Chemical Bonding material for 6 hours of lessons with 2 meetings. After finishing the lesson, a post-test was given to determine the increase in student learning outcomes. The final test of the first cycle of action was obtained by students who did not achieve the minimum completeness criteria (KKM) totaling 8 people (28.57%) while students who achieved the completeness criteria scores were 20 people (71.43%), the results of the observation were that there were research activities in the action Cycle I achieved a score of 90% and the results of observing student activities reached 83.75%. While the final test of the second cycle of action obtained students who did not achieve the minimum completeness criteria (KKM) totaled 3 people (10.72%) while students who achieved the completeness criteria scores were 25 people (89.28%), the results of observations on the activities of researchers in The second cycle of action obtained a score of 94.2% and the results of observing student activities reached 93.75%. Thus, it can be concluded that the Numbered Heads Together (NHT) learning model can improve student learning outcomes on Chemical Bonding material in class X SMK Negeri 1 Gandapura. Keywords: Numbered Heads Together (NHT) Learning Model, Student Learning Outcomes, Chemical Bonds Abstrak: Penerapan Pembelajaran Numbered Heads Together (Nht) Untuk Meningkatkan Hasil Belajar Siswa Kelas X Pada Materi Ikatan Kimia di Smk Negeri 1 Gandapura. Penelitian ini dilakukan dengan cara memberikan pre-test pada siswa untuk mengetahui kemampuan awal siswa sebelum pembelajaran, selanjutnya dikenakan perlakuan model pembelajaran Numbered Heads Together (NHT) pada materi Ikatan Kimia selama 6 jam pelajaran dengan 2 kali pertemuan. Setelah selesai pembelajaran, diberikan post-test untuk mengetahui peningkatan hasil belajar siswa. Tes akhir tindakan siklus I diperoleh siswa  yang tidak  mencapai nilai kriteria ketuntasan minimal (KKM) berjumlah 8 orang (28,57%) sedangkan siswa yang mencapai nilai kriteria ketuntasan berjumlah 20 orang (71,43%), hasil observasi terdapat aktivitas peneliti pada tindakan siklus I mencapai skor 90% dan hasil observasi aktivitas siswa mencapai 83,75%. Sedangkan tes akhir tindakan siklus II diperoleh siswa  yang tidak  mencapai nilai kriteria ketuntasan minimal (KKM) berjumlah 3 orang (10,72%) sedangkan siswa yang mencapai nilai kriteria ketuntasan berjumlah 25 orang (89,28%), hasil observasi terhadap aktivitas peneliti pada tindakan siklus II memperoleh skor 94,2% dan hasil observasi aktivitas siswa mencapai 93,75%. Dengan demikian dapat disimpulkan bahwa model pembelajaran Numbered Heads Together (NHT) dapat meningkatkan hasil belajar siswa pada materi Ikatan Kimia di kelas X SMK Negeri 1 Gandapura Kata Kunci: Model Pembelajaran Numbered Heads Together (NHT), Hasil Belajar Siswa, Ikatan Kimia
Keywords: Model Pembelajaran Numbered Heads Together (NHT); Hasil Belajar Siswa; Ikatan Kimia